HYGIENE SANITASI DAN PERILAKU PENJAMAH MAKANAN DENGAN ANGKA KUMAN PADA MAKANAN JAJANAN DI LINGKUNGAN SEKOLAH - Trigunarso, Sri Indra (Jurnal Kesehatan, 2020)
One of the community services in the field of food, is hawker food whose existence is often still far from meeting health requirements so that the impact of the disease on the community. By seeing the potential of such large food and high levels of vulnerability, efforts should be made to monitor the quality of food management by observing hygiene and sanitation rules and health requirements. The purpose of this study was to determine the relationship between sanitation hygiene and behavior of the handlers with the number of germs on snacks in the surroundings of the Kartika Jaya Foundation School in Bandar Lampung City. This type of research is analytic descriptive, with the cross-sectional approach. The population in this study is all traders and food sold in the environment around the school both inside and outside the school building. Samples were taken based on the determination of the sample criteria of traders and food, totaling 53 traders. The method used is a laboratory test on the number of germs on food samples and hand-held swabs by the ALT (Total Plate Number) method as well as questionnaires and observations. Data analysis was performed univariately and bivariate (using the chi-square test ?=0,05). From the results of this study it can be concluded that there is a relationship between sanitation hygiene (?-value=0,0001) and food handler behavior (?-value=0,004) with the number of germs on snacks in the surroundings of the Kartika Jaya Foundation School in Bandar Lampung City.